Multiple warty dyskeratomas: case report. - Nesrin Ugras; Saduman Balaban Adim; Mehtap Kilicoglu; Emel Bülbül Baskan (Tehran University of Medical Sciences, 2014)
Warty dyskeratoma is a rare tumor that presents mainly as an isolated papule or nodule on the scalp, face or neck in the adults. Warty dyskeratoma frequently arises as a single lesion with a central keratotic plug on the skin of middle-aged or elderly people. Multiple warty dyskeratomas are very rare cutaneous lesions which are mostly seen on the scalp. We herein report a multiple warty dyskeratoma in a female patient.